(untitled) (Bangladesh Journal of Medical Science, 2024)
Medical students face numerous challenges due to demanding academic and environmental requirements set by educational institutions, society, and families. International medical students, in addition, grapple with further hurdles related to their acculturation in a foreign country, including isolation from their family and friends, language and cultural barriers, and individual factors. Although a body of knowledge addresses stressors typical for international medical students in other countries, insufficient attention has been given to this issue in Malaysia, which has recently emerged as an educational hub and a favored destination for young people aspiring to study medicine. It is vital to consider the academic, cultural, and religious aspects of the countries international students come from in the context of their potential acculturative dynamics in the host country. This paper explores factors contributing to stress among international medical students in Malaysia and examines common coping mechanisms relevant to this unique student population. The role of social, institutional, and professional support, religion, language, and personal development has been highlighted. Emphasizing the need for further research to inform tailored interventions aimed at alleviating stress among international medical students and enhancing the educational environment in Malaysian medical schools is crucial. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 877-884